The implementation of national curriculum and Islamic boarding school curriculum integration - Maghfiroh, Rofi Atina; Ali, Mohamad; Azani, Mohamad Zakki (Universitas Pendidikan Indonesia, 2023)
The relationship between religion and science is an interesting debate to discuss. The thing that often becomes the point of the problem is the integration between the two. The question is when religion becomes a source of spirit for the development of science and how the two sciences can meet. There is an essential component in the educational process, namely the curriculum. Because the curriculum applied in Indonesia is more oriented to secular Western concepts, it is necessary to integrate religious education with general education. More than that, the question often arises is whether the integration is a form of dissolution or mixing. By a phenomenological approach with descriptive analysis techniques, this research concludes that the integration of the curriculum at the KMI level at Pondok Pesantren Jajar Islamic Center Surakarta can be categorized in the form of dissolution, however in applying this form is not perfect yet; therefore, a review is needed, especially in the implementation of an integrative Curriculum Lesson Plan.Hubungan antara agama dan sains menjadi perdebatan yang menarik untuk dibahas. Hal yang sering menjadi titik permasalahan adalah integrasi antara keduanya. Pertanyaannya adalah kapan agama menjadi sumber ruh bagi perkembangan ilmu pengetahuan dan bagaimana kedua ilmu tersebut dapat bertemu. Ada komponen penting dalam proses pendidikan, yaitu kurikulum. Karena kurikulum yang diterapkan di Indonesia lebih berorientasi pada konsep sekuler Barat, maka perlu dilakukan integrasi pendidikan agama dengan pendidikan umum. Lebih dari itu, pertanyaan yang sering muncul adalah apakah integrasi itu merupakan bentuk pembubaran atau pencampuran. Dengan pendekatan fenomenologi dengan teknik analisis deskriptif, penelitian ini menyimpulkan bahwa integrasi kurikulum tingkat KMI di Islamic Center Pondok Pesantren Jajar Surakarta dapat dikategorikan dalam bentuk disolusi, namun dalam penerapan bentuk tersebut belum sempurna; Oleh karena itu, diperlukan adanya peninjauan kembali khususnya dalam implementasi RPP Kurikulum integratif.